Diclofenac Abatement using Modified Solar Photo-Fenton Process with Ammonium Iron(III) Citrate - Trovo, Alam G. [UNESP]; Nogueira, Raquel Fernandes Pupo [UNESP] (Soc Brasileira Quimica, 2011)
The influence of pH on the degradation of the pharmaceutical diclofenac (DCF) by the solar/photo-Fenton process was investigated using ammonium iron(III) citrate complex (FecitNH(4)). Although the degradation efficiency decreased as the pH increased (in the pH range 5 to 8), the DCF concentration was lower than its limit of detection after 45 min irradiation while 77% of the total organic carbon was removed after 150 min irradiation at initial pH 7 (without further adjustment). A pseudo-first-order kinetics of DCF degradation was observed, which kinetic constant increased with the increase of the concentrations of FecitNH(4) and H(2)O(2). Lower DCF degradation was observed when present in a sewage treatment plant (STP) effluent sample, mainly due to the high concentration of carbonate and bicarbonate at pH 7. However, after adjusting the pH to 5, the DCF concentration was lower than its detection limit after 75 min irradiation.
Keywords: pharmaceutical; wastewater; advanced oxidation process; iron complex